CREATION OF AN APPROACH FOR DETERMINING OPTIMAL LOCOMOTIVE OPERATION MODES EMPLOYING CONTINUOUS DYNAMIC PROGRAMMING (Ta'limning zamonaviy transformatsiyasi, 2024)
This article delves into the formulation of an innovative technique for ascertaining optimal locomotive operational modes utilizing continuous dynamic programming (CDP). The research endeavors to address the pressing demand for adept and adaptive methodologies within train control systems. Through an exhaustive scrutiny of existing literature, the article establishes a comprehensive context by investigating prior research pertaining to locomotive operational modes and their associated optimization strategies. The research methodology section meticulously delineates the systematic approach undertaken in the creation and validation of the proposed method. Following this, the analysis and results section elucidates findings derived from the practical application of the developed method, providing insights into its efficacy in determining optimal locomotive operational modes. The concluding segment succinctly encapsulates pivotal insights, underscores the contributions of the study, and propounds potential avenues for subsequent research endeavors within this progressive domain.